2015
DOI: 10.1097/01.j.pain.0000461289.65571.54
|View full text |Cite
|
Sign up to set email alerts
|

Disease-related differences in resting-state networks

Abstract: Localized provoked vulvodynia (LPVD) affects approximately 16% of the female population, but biological mechanisms underlying symptoms remain unknown. Like in other, often comorbid chronic pain disorders, altered sensory processing and modulation of pain, including central sensitization, dysregulation of endogenous pain modulatory systems, and attentional enhancement of pain perception have been implicated. The aim of this study was to test whether regions of interest showing differences in LPVD compared to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 80 publications
2
40
1
Order By: Relevance
“…Indeed, there is growing reproducible evidence that resting state activity in many chronic pain conditions show a variety of abnormalities (Baliki et al, 2008; Baliki et al, 2014b; Bolwerk et al, 2013; Cauda et al, 2010; Cauda et al, 2009; Gupta et al, 2015; Loggia et al, 2013; Malinen et al, 2010). The most consistent result is a disruption of the default mode network, specifically a dissociation of its prefrontal component in many different types of chronic pain.…”
Section: Chronic Pain and Resting State Brain Activitymentioning
confidence: 99%
“…Indeed, there is growing reproducible evidence that resting state activity in many chronic pain conditions show a variety of abnormalities (Baliki et al, 2008; Baliki et al, 2014b; Bolwerk et al, 2013; Cauda et al, 2010; Cauda et al, 2009; Gupta et al, 2015; Loggia et al, 2013; Malinen et al, 2010). The most consistent result is a disruption of the default mode network, specifically a dissociation of its prefrontal component in many different types of chronic pain.…”
Section: Chronic Pain and Resting State Brain Activitymentioning
confidence: 99%
“…While shared brain mechanisms between different chronic pain disorders have been postulated, recent findings suggest some alterations in functional connectivity may also show disease specificity. 23 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported functional connectivity disturbances in medial brain motor areas in women with interstitial cystitis/painful bladder syndrome [9], in men with chronic prostatitis/chronic pelvic pain syndrome [10], and also in women with localized provoked vulvodynia [7]. Recent anatomical connectivity studies in rats using the retrograde transneuronal labelling studies suggest that visceral structures may be more strongly represented in medial brain motor areas than any other cortical area; also, the visceral representation in motor cortex is aligned with the more medial somatic motor representation of trunk and lower limb muscles [12].…”
mentioning
confidence: 99%